Pengaruh Jaminan Hari Tua dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan Pada PT Delima Pinglogistra Jakarta - Ahmad Yani; Siti Novi Oktaviani; Dewi Kania (Prosiding Amal Insani Foundation, 2023)
This study aimed to find out and analyze whether there is a significant influence between the effect of old age security and occupational health on employee productivity partially or simultaneously. This research uses a quantitative approach. As for the population in this study, there were 103 employees of PT Delima Pinglogistra Jakarta, while the sample with the sampling technique was saturated, so the samples were taken entirely from the total population with a sample of 103 employees. The results of this study are old age security has a significant effect on work productivity, and occupational health has a considerable impact on work productivity, and Old Age Security and occupational health have a significant effect on work productivity (Y) PT Delima Pinglogistra Jakarta.